Synthesis of slow-release fertilizer with coconut shell biochar and activated natural zeolite for red onion (Allium ascalonium) - Permana, Edwin; Aulia, Kiranti; Aziz, Herman; Murti, Sri Djangkung Sumbogo (Journal of Degraded and Mining Lands Management, 2023)
Using fertilizers is one of the efforts to increase crop productivity, but conventional fertilizers tend to be easily leached so it becomes ineffective. Slow-release fertilizer (SRF) is a modified fertilizer that releases nutrients slowly or gradually so that the use of fertilizer becomes more effective. SRF can be synthesized by mixing fertilizers with zeolite as a slow-release agent. Because natural zeolite contains many impurities that cover the pores of the zeolite, it is necessary to carry out an activation process to increase the pore capacity of the zeolite so that the process of absorption of nutrients in the SRF becomes more leverage. This study aimed to synthesize NPKSMg slow-release fertilizer with coconut shell biochar and activated natural zeolite for red onion plants (Allium ascalonium). Coconut shell biochar was used as a source of potassium. The activation process of natural zeolite was carried out by the desilication method using a basic solution of NaOH as an activator. Based on the results of research using activated natural zeolite on SRF, the surface structure of SRF became more porous, with a porosity percentage of 69.31%. In addition, the use of activated natural zeolites increased the absorption of nutrients in fertilizers. The use of biochar in SRF increased the percentage of porosity by 66.32%. The use of coconut shell biochar as a matrix and activated natural zeolite as a slow-release agent in SRF NPK S Mg for red onion plants has succeeded in increasing red onion yields.